Early Detection of Fraud with an Accounting System - Sopanah, Ana; Rusdianti, Imanita Septian; Sulistyan, Riza Bahtiar (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2025)
This research focuses on the implementation of an accounting system that is able to detect and minimize fraud, where this accounting system is one of the components of internal control according to COSO. This research is qualitative research with a descriptive approach through interviews, observation and documentation. Interviews were conducted with 26 informants, namely employees of PT. Ciomas Adisatwa, Tbk who serves as unit head, finance accounting unit, technical service, cashier, production admin, unit sales, sales admin and unit logistics. The research results revealed that the implementation of the accounting system at PT. Ciomas Adisatwa, Tbk makes it easy for users, integrated in real time and has tiered authorization. The role of information systems in preventing and detecting fraud is through fairness or standardization parameters and data input time reports. The accounting system as a component of internal control, implies that the internal control indicators in the accounting system implemented by PT. Ciomas Adisatwa, Tbk has been fulfilled. The practical implications of this research are that: the CPS/CPR application used can produce accurate and up-to-date profit and loss reports, and can provide early detection of indications of fraud